The effect of haemoglobin, albumin, lymphocyte and platelet score on the prognosis in patients with multiple myeloma - Solmaz, Şerife; Uzun, Özcan; Sevindik, Ömür Gökmen; Demirkan, Fatih; Özcan, Mehmet Ali; Özsan, Güner Hayri; Alacacıoğlu, İnci (John Wiley and Sons Inc, 2023)
Introduction In multiple myeloma cases, a variety of prognostic parameters have been identified, which contain the Durie-Salmon classification and the international staging system (ISS) that takes the serum ss2 microglobulin and albumin levels, platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and monocyte-to-lymphocyte ratio (MLR). This study investigates the effect of haemoglobin, albumin, lymphocyte and platelet (HALP) score which is a marker of inflammation status and nutrition, at the time of diagnosis for the patients with multiple myeloma on prognosis. Methods A total of 200 multiple myeloma patients with HALP scores calculated from serum haemoglobin, albumin, lymphocyte count and platelet levels at the time of diagnosis were retrospectively examined. The effect of HALP score on overall survival (OS) and progression-free survival and its relationship between the previously evaluated prognostic parameters were investigated. Results The optimal cut-off value with the ROC curves for the HALP score was 28.8. The patients were divided into two groups according to the optimal value of the HALP score (low-score group: HALP <= 28.8 [n: 134] and high-score group HALP >28.8 [n: 66]). In the group with the high HALP score, the OS was statistically longer than the low HALP score group (84 months and 53 months; p = 0.0001). In addition, when the effects of NLR, PLR, HALP score and ISS stage on OS were examined by multivariate analysis, all these markers were found to be statistically significant predictors. Conclusions HALP score may be a valuable prognostic marker for patients with multiple myeloma.
Keywords: HALP Score; Multiple Myeloma; Overall Survival; Prognosis; Progression-Free Survival